Enhancing the efficiency of e-commerce through digital technologies: Economic and legal aspects - Volynets, Vitalii; Sysoiev, Dmytro; Kotsur, Andrii; Murenets, Iryna; Kyrylenko, Serhiy (Edelweiss Applied Science and Technology, 2024)
The research is aimed at analyzing the economic and legal aspects of the functioning of digital technologies in the field of electronic commerce, as well as studying the impact of these technologies on the efficiency of processes and their interaction with various aspects of legislation regulating the field of electronic commerce. In the course of the research, literary sources and legal acts were analyzed with the aim of generalizing approaches to understanding electronic commerce and establishing the main principles of its regulation. The analysis of statistical data made it possible to identify trends in the development of the e-commerce market and the influence of negative external factors. In turn, the application of methods of generalization and systematization made it possible to determine the key aspects of the implementation of digital technologies to increase the efficiency of electronic commerce and identify regulatory gaps in this area. The results of the research confirm that e-commerce in Ukraine plays an important role in the digital economy, ensuring efficiency and profitability for businesses. An analysis of the e-commerce market showed the growth of the use of the Internet for shopping, even in difficult socio-political conditions. Therefore, despite the challenges facing the country, e-commerce remains a sustainable and powerful tool for business development and consumer activity. However, it is necessary to improve the legal framework in order to meet the requirements of modernity and to ensure the protection of consumers’ and market participants’ rights from technical and other risks related to electronic commerce.